2021
DOI: 10.3390/vaccines9010043
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapeutic Strategies for Neuroblastoma: Present, Past and Future

Abstract: Neuroblastoma is the most common extracranial pediatric solid tumor with a heterogeneous clinical course, ranging from spontaneous regression to metastatic disease and death, irrespective of intensive chemotherapeutic regimen. On the basis of several parameters, children affected by neuroblastoma are stratified into low, intermediate and high risk. At present, more than 50% of high-risk patients with metastatic spread display an overall poor long-term outcome also complicated by devastating long-term morbiditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 138 publications
(194 reference statements)
0
27
0
Order By: Relevance
“…Patients were grouped and staged according to the INRG classification and staging system (19,20). The clinical stage of the patients was confirmed by fluorodeoxyglucose positron emission tomography, computerized tomography and/or metaiodobenzylguanidine (MIBG) scan in addition to other methods such as bone marrow biopsy, bone scan, cranial magnetic resonance imaging and ultrasonic examination (18).…”
Section: Patientsmentioning
confidence: 99%
“…Patients were grouped and staged according to the INRG classification and staging system (19,20). The clinical stage of the patients was confirmed by fluorodeoxyglucose positron emission tomography, computerized tomography and/or metaiodobenzylguanidine (MIBG) scan in addition to other methods such as bone marrow biopsy, bone scan, cranial magnetic resonance imaging and ultrasonic examination (18).…”
Section: Patientsmentioning
confidence: 99%
“…A recent update from a phase III trial (HR-NBL1/SIOPEN) demonstrated no additional benefit and added toxicity with interleukin (IL)-2 when given with dinutuximab to patients with high-risk neuroblastoma [19], leading to discontinuation of use of IL-2 in similar COG protocols. Other recent advances with anti-GD2 antibodies in neuroblastoma are reviewed elsewhere [20].…”
Section: Disialoganglioside Gd2mentioning
confidence: 99%
“…In recent years, harnessing the body's own immune system via immunotherapies has proven to be an effective strategy in many cancer types, [ 3 ] and addition of immunotherapy agents to existing cytotoxic regimens has demonstrated improved outcomes for patients with neuroblastoma. [ 3 6 ]…”
Section: Introductionmentioning
confidence: 99%